2009
DOI: 10.1007/s11146-009-9197-8
|View full text |Cite
|
Sign up to set email alerts
|

House Prices and Economic Growth

Abstract: Economic growth, House prices, Wealth effect, Collateral effect, Common correlated effects estimators, Long horizon predictability, E23, E24, R11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 25 publications
3
63
0
3
Order By: Relevance
“…A number of studies, (Kapopoulos and Siokis (2005), Ebrahim and Hussain (2010)) confirm that, ceteris paribus, real estate exposure is negatively related to stock and other risky financial asset holdings. Miller et al (2009) show that after controlling for wealth, income and other household characteristics, the relative share of risky assets is a negative function of the real estate ownership in the US. By contrast, Kapopoulos and Siokis (2005) find that in the case of Greece real estate prices, at least in Athens area, are a function of the General Index of the Athens Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 95%
“…A number of studies, (Kapopoulos and Siokis (2005), Ebrahim and Hussain (2010)) confirm that, ceteris paribus, real estate exposure is negatively related to stock and other risky financial asset holdings. Miller et al (2009) show that after controlling for wealth, income and other household characteristics, the relative share of risky assets is a negative function of the real estate ownership in the US. By contrast, Kapopoulos and Siokis (2005) find that in the case of Greece real estate prices, at least in Athens area, are a function of the General Index of the Athens Stock Exchange.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Few exceptions that we are aware of include: Leung (2003), Demary (2010), Miller et al, (2011), Simo-Kengne et al, (2012 and Nyakabawo et al, (2013). Leung (2003) developed a simple endogenous growth model to show that economic growth can induce the real house price growth; but this theoretical result need to be assessed empirically.…”
Section: Introductionmentioning
confidence: 99%
“…Leung (2003) developed a simple endogenous growth model to show that economic growth can induce the real house price growth; but this theoretical result need to be assessed empirically. Miller et al, (2011) applied a Common Correlation Error (CCE) model on metropolitan data and found that house price changes in the US affect significantly per capita GDP growth. Using panel time series methodology, similar result was found by Simo-Kengne et al, (2012), who reported a significant positive effect of house price appreciation on economic growth at both national and provincial levels in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Many economists argue that these events caused the recent dramatic changes in the behavior of financial and economic markets (Miller et al, 2011), even extending to global financial markets and economies. A growing literature recognizes the importance of the relationship between the housing market and the macro economy, showing that the interaction between house prices and economic growth imbeds important policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…Economists and policy makers seemingly agree that house prices play an important role in stimulating the growth or decline of an economy. Miller et al, (2011) suggest that the strong housing market during the 2001 stock market crash may have saved the U.S. economy from a severe recession and that, in addition, the recent collapse of the housing market initiated he Great Recession. The housing market, thus, plays an important role in the economy and its performance affects its overall performance.…”
Section: Introductionmentioning
confidence: 99%